Will the renminbi emerge as a safe-haven currency? Evidence from the tiger cub economies’ stock market volatility from 2016 to 2021 - Delfin, Paolo Manuel D. (Animo Repository, 2022)
There will always be uncertainty and risks involved in markets due to change, and it is full of obscure information. Investors or other finance professionals need to have backups during market fluctuations. It is also vital to ensure that every possible safe-haven currency in certain countries or areas is well-studied. The primary purpose of this research is to measure any safe-haven properties that the Chinese Renminbi holds among the Tiger Cub Economies and its stability against stock market volatility using the DCC-GARCH model. In addition, the study also forecasts any safe-haven property the Chinese Renminbi may hold into the future by one year using the study’s statistical model. The research results show that the Chinese Renminbi does not possess any safe-haven properties during most periods but exhibits weak safe-haven properties in the pre-pandemic period in the Philippine and Vietnamese markets. Furthermore, the results show that the Chinese Renminbi can be used to hedge against the Philippines and Vietnam countries. However, the Chinese Renminbi for the countries of Indonesia, Thailand, and Malaysia performed poorly and was not suitable for investing during market turmoil. Lastly, for the forecasting, the Philippine and Vietnamese markets exhibited decorrelations from the market, which showed good hedging abilities that investors may take advantage of.